Ovarian development, spawning season, size at maturity and fecundity of Acentrogobius viridipunctatus (Valenciennes, 1837) in the Vietnamese Mekong Delta - Quang Minh Dinh; Ton Huu Duc Nguyen; Ngon Trong Truong; Diep Xuan Doan; Tien Thi Kieu Nguyen (PeerJ, 2022)
This present study provides an overview of the reproductive traits, including ovarian development, spawning season, size at maturity (Lm), and fecundity of Acentrogobius viridipunctatus – a high economic value fish in the Vietnamese Mekong Delta (VMD). A total of 432 females were collected using trawl nets from January to December 2020 at four sites, including Long Huu-Tra Vinh (LHTV), Trung Binh-Soc Trang (TBST), Dien Hai-Bac Lieu (DHBL), and Tan Thuan-Ca Mau (TTCM). The ovarian diameter was seen to increase from 2.09 (stage I) to 6.57 mm (stage V). Histological analysis showed that the goby was a multi-spawner due to the different oocyte stages found in stages IV and V of ovaries. It can release eggs all year-round due to the monthly appearance of ovarian stages IV and V during the study period, with the main peak in the 2–4 months of the wet season noted with the highest value of gonadosomatic index at that time. The Lm increased from 6.6 cm at TBST to 9.4 cm at TTCM. This species displayed relatively high fecundity, ranging from 5,481 to 130,683 eggs/female. The average fecundity of this fish was 27,698 ± 7,983 eggs/female at LHTV, 46,592 ± 7,264 eggs/female at TBST, 23,271 ± 4,985 eggs/female at DHBL, and 31,408 ± 2,515 eggs/female at TTCM. Egg diameter ranged from 0.45 ± 0.01 at DHBL to 0.50 ± 0.01 at TBST. For sustainable exploitation, local governments should ask the fishers to avoid catching fish during the main spawning period, and the fish length at first capture should be >Lm.